TEACHING ROBOTICS AT PRIMARY SCHOOLS - HYKSOVA, Hana; STOFFOVA, Veronika (Trends in education, 2022)
Robots, robotics, robotic toys and robotic kits are a much-discussed topic in today's education. How to include robotics in the teaching process? In which years to include robotics? What robotic toys or kits to use in teaching? In which subjects and areas to implement robotics? Is robotics part of the Framework and School educational programs? Why include robotics in the teaching process? These are issues that are currently being addressed by many primary and secondary school teachers. We will not stop technological progress and development. Robotics is a field that is developing very fast. Robots are an integral part of our lives and helpers in various fields and households. Due to the huge shortage of workers in some fields, robots are also beginning to replace human factors. Today, robotic toys and kits are one of the ways to start building a relationship with technology and robotics in children in kindergarten, primary school, high school or university.
Keywords: robotics; robotic toys; robotic kits; teaching; robot programming